Changes in the labour market and their consequences - Niedzielski, Eugeniusz (Olsztyn Economic Journal, 2019)
The study presents the characteristics of changes in the labour market, their causes and effects. The subjects under consideration are the consequences of technological and demographic changes, their impact on the size and structure of labour demand and on the employee-employer relationship. The relationship between these changes in the context of the role of work and employment in human life was discussed.